Caste and Gender in Arundhati Roy`s The God of Small Things - Saeed , Bayar (Humanities Journal of University of Zakho, 2021)
In this study, I focus primarily on gender and caste issues and their effects on the agonized inner mind of the repressed female and child characters in the novel The God of Small Things (1997) by Arundhati Roy. In this novel, Indian woman novelist Arundhati Roy focused primarily on the existential psychological predicaments and travails in the lives of the subjugated Indian women who were imperiled by the psychological and physical abuse in a male-dominated society ruled by rigid social and religious conventions and constraints. In other words, Roy sought to appraise the aberrant psychology of men and women in the conventional Indian social climate. She focused on the traumatic experiences of her women characters under the impact of social class and gender discrimination. She employed Freud's psychoanalytic theory to reveal the disturbed psyche of her women characters. The methodology of this study concerns two major directions: close-text analysis and cultural studies. It deals with sociological and psychological problems, which analyze and expose the symbolism of man’s behavior particularized in a patriarchal society.